Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 7 - Section 7.5 - Multiplying with More Than One Term and Rationalizing Denominators - Exercise Set - Page 551: 113



Work Step by Step

$(3-\sqrt{13})^{2}=3^{2}-2\cdot 3\cdot\sqrt{13}+(\sqrt{13})^{2}\\\\=9+13-6\sqrt{13}\\\\=22-6\sqrt{13}$ $f(3-\sqrt{13})=22-6\sqrt{13}-6(3-\sqrt{13})-4$ $= 22-6\sqrt{13}-18+6\sqrt{13}-4$ ... add like terms $=0$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.